2017
DOI: 10.1136/bmjopen-2016-014210
|View full text |Cite
|
Sign up to set email alerts
|

Healthier central England or North–South divide? Analysis of national survey data on smoking and high-risk drinking

Abstract: ObjectivesThis paper compares patterns of smoking and high-risk alcohol use across regions in England, and assesses the impact on these of adjusting for sociodemographic characteristics.DesignPopulation survey of 53 922 adults in England aged 16+ taking part in the Alcohol and Smoking Toolkit Studies.MeasuresParticipants answered questions regarding their socioeconomic status (SES), gender, age, ethnicity, Government Office Region, smoking status and completed the Alcohol Use Disorders Identification Test (AUD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 51 publications
(60 reference statements)
2
31
0
1
Order By: Relevance
“…Black groups (Fuller 2015). Similar findings were reported for high risk drinking status using the Alcohol Toolkit Studies, the 'Mixed/multiple' group having a relative risk compared with the White group of 0.87; the Asian (0.08), Black (0.25), and Other (0.42) groups were all statistically significantly at lower risk (Beard et al, 2017).…”
Section: Health Behaviourssupporting
confidence: 75%
See 1 more Smart Citation
“…Black groups (Fuller 2015). Similar findings were reported for high risk drinking status using the Alcohol Toolkit Studies, the 'Mixed/multiple' group having a relative risk compared with the White group of 0.87; the Asian (0.08), Black (0.25), and Other (0.42) groups were all statistically significantly at lower risk (Beard et al, 2017).…”
Section: Health Behaviourssupporting
confidence: 75%
“…While there has been increased reporting of smoking prevalence by ethnic group, the use of a single 'mixed' group is a major drawback. For example, using pooled data for England from the Smoking Toolkit Study (2014-16, n=53,922), Beard et al (2017) show that the mixed/multiple group had a greater adjusted risk of smoking (RR 0.96, 95% CI, 0.83-1.11) than the Asian (0.41, 0.38-0.45) or Black (0.40, 0.35-0.46) groups, compared to the White reference group. According to ONS' UK analysis of the 2014 Integrated Household Survey, current smoking rates in the mixed/multiple group were 29.4% for males and 19.2% for females, higher than for any other ethnic group (only Asians being broken down into their 2011 census categories) (ONS 2015).…”
Section: Health Behavioursmentioning
confidence: 99%
“…9, 10 A North-South divide in smoking prevalence was identified in household population survey data (2014-2016) with rates highest in the North East and lowest in the South East. 11 fractures over this period. 7 We reported that hip fracture incidence has decreased over time in women and increased in men; 7 an observation that has been supported by a recent analysis of UK CPRD data which showed that hip fracture incidence had similarly increased in men but plateaued in women.…”
Section: Discussionmentioning
confidence: 83%
“…Besides the known regional differences in income and SES, significant regional differences have been reported for mental 13 and physical 14 health problems. Regional differences in wealth and health are likely linked to each other, [15][16][17] and have been shown to be partly driven by migration. 14,18 If genome-wide complex trait variation is geographically clustered, this should also be taken into account in certain genetically-informative study designs.…”
mentioning
confidence: 99%